Role of Andean Community of Nations in South-American integration process - Aronová, Barbora; Adamcová, Lenka; Honajzrová Banús, Shirley C.; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2008)
First chapter of this diploma thesis discusses foundation, historical background and contemporary situation of Andean Community of Nations. Second chapter describes Andean Integration System and role of individual bodies and institutions that form this system. Third chapter pays attention to role of Andean Community of Nations in South-American integration process and it's relation to other integration blocs in South America -- Common Market of the South, Union of South-American Nations and Bolivarian Alternative for Latin America and the Caribbean. Fourth chapter evaluates impact of Andean integration process on economic and trade development in member countries.
Vedoucí práce: Lenka Adamcová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2009
Rok obhajoby 2009
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses